Territorialidade de espaço público em uma cidade ribeirinha na Amazônia Setentrional Brasileira – Afuá, Pará - José Marcelo Martins Medeiros; Jacy Côrrea Neto; Mariana Martins Medeiros (Confins)
The Brazilian Amazon manifests itself in various urban spatial forms. In this context, the understanding of the urban phenomena allows the recognition of the contemporary appropriations and the apprehension of the daily life. This research investigates the public space of the riverside town of Afua (Marajo Archipelago, State of Para, Brazil), a city structured under wooden stilt system that does not allow traffic from motor vehicles. This research seeks to understand the appropriation of the city river’s banks through the notion of territoriality. The data from this research also allowed the construction of a proposal of urban intervention, using the interface between the territory and the design of public space. The research has quantitative and qualitative characteristics, questionnaires have been applied, and references have been collected as well as a field survey (with land-use mapping techniques, photographic recordings and data collection). Theories on the concept of territory, in particular those of Raffestin (1993, 2003), allowed the preparation of structured analyzes in two aspects: urban and socio-territorial, which can in future support the design of an urban intervention, in order to promote local development.